Mapping a pluralistic continuum of approaches to digital disconnection - Ross, Morgan Quinn; Gilbert, Alicia; Klingelhöfer, Julius; Matassi, Mora; Nassen, Lise-Marie; Van Bruyssel, Sara; Verlinden, Alice; Parry, Douglas A (Media Culture & Society, 2024)
The study of digital disconnection – the voluntary non-use of digital media – is a growing research domain characterized by increasingly pluralistic approaches. To map this diverse terrain, we offer an analytical heuristic: a continuum of approaches to digital disconnection. This tool proposes one primary dimension – viewing digital disconnection as individually functional to socially meaningful (ontology) – and two secondary, concomitant dimensions – holding post-positive to interpretivist perspectives on knowledge generation (epistemology) as well as applying quantitative to qualitative methods (methodology). We offer examples of scholarship along the continuum and advocate for the complementarity of different approaches. Although the continuum is not a universal framework, it provides a tool for scholars to review the domain and for digital disconnection researchers specifically to locate themselves on and build bridges across the continuum. We hope that this continuum supports and expands the pluralistic nature of digital disconnection scholarship into the future.<br